Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Anak Usia 2-5 Tahun di Puskesmas Ubud 1 Gianyar - Komang Triyani Kartinawati; I Wayan Darwata; Ni Kadek Ratih Riska Yanti (Aesculapius Medical Journal, 2022)
[Factors Influencing The Incidence Of Stunting In Children Aged 2-5 Years At The Ubud 1 Gianyar Public Health Center] Stunting is a chronic nutritional disease caused by inadequate nutritional intake during the growth period. The diagnosis of stunting is made if the Z-score of length or height per age is less than -2 SD (Standard Deviation) based on the WHO child growth standard. This study aims to explain the factors that influence the incidence of stunting in children aged 2-5 years at the Ubud 1 Gianyar Public Health Center. This research was carried out in the working area of the Ubud 1 Health Center, Gianyar in January-June 2022. This study was a quantitative analytic study with a case-control design, which used 60 samples, consisting of 30 cases and 30 controls. Sampling was collected with a consecutive sampling technique, where all subjects who met the inclusion criteria were included in the study until the required number of samples were met. Data was collected by measuring height, interviews and filling out questionnaires. The research was analyzed by univariate, bivariate, and multivariate. Based on the Chi-square test, there was a significant relationship between the level of feeding patterns (p-value 0.038), exclusive breastfeeding pattern (p-value 0.000), parental education (p-value 0.001), infectious diseases (p-value 0.019). However the utilization of health services could not be measured in this study. This study concluded that the nonexclusive breastfeeding pattern was the most influential factor in the incidence of stunting compared to other risk factors (odds ratio = 9,333). Further research is needed with a mixed method approach in order to obtain better analytical results in assessing the effect on stunting. Keywords : stunting, children 2-5 years, risk factors, case-control